IMPLEMENTASI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM MENINGKATKAN HASIL BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA - I Komang Sukendra; I Wayan Muliana; I Made Surat (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
STAD type cooperative learning emphasizes collaboration in groups, student-centered learning and awards for the best team will make students more active and enthusiastic, especially activities in communicating with fellow study groups. The purpose of this study was to determine the increase in learning outcomes with the application of cooperative learning models in flat and spatial geometry courses in improving student learning outcomes. This type of research is action research with qualitative data. In this action research done collaboratively. The subjects of this study were students of Mathematics Education in the fourth semester of PGRI Mahadewa University, Indonesia, for the 2023/2024 academic year. The object of research is the application of the STAD type cooperative learning model and student learning outcomes in the subject of flat and spatial geometry. The research was carried out in two cycles and each cycle consisted of four stages, namely planning, implementing, observing, and reflecting. The results of the action show that the results of cycles I and II and their supporting factors so that the application of the STAD type cooperative learning model in flat and spatial geometry courses can improve student learning outcomes.